Brodalumab for the treatment of plaque psoriasis in a real-life setting: a 3 years multicenter retrospective study—IL PSO (Italian landscape psoriasis) - Gargiulo, Luigi; Ibba, Luciano; Malagoli, Piergiorgio; Amoruso, Fabrizio; Argenziano, Giuseppe; Balato, Anna; Bardazzi, Federico; Burlando, Martina; Carrera, Carlo Giovanni; Damiani, Giovanni; Dapavo, Paolo; Dini, Valentina; et al. (Frontiers in Medicine, 2023)
Introduction Brodalumab is a monoclonal antibody that targets the subunit A of the interleukin-17A receptor (IL17RA), inhibiting the signaling of various isoforms of the IL-17 family. It has been approved for the treatment of moderate-to-severe plaque psoriasis after being evaluated in three Phase-3 trials. However, long-term data on brodalumab in a real-life setting are still limited. Methods The aim of this study was to evaluate the long-term effectiveness and safety of brodalumab in psoriasis. We also assessed the drug survival of brodalumab in a 3 years timespan. We conducted a retrospective multicenter study on 606 patients followed up at 14 Italian dermatology units, all treated with brodalumab according to Italian guidelines. Patients’ demographics and disease characteristics were retrieved from electronic databases. At baseline and weeks 12, 24, 52, 104 and 156, we evaluated the psoriasis area and severity index (PASI) score and investigated for adverse events. The proportions of patients reaching 75, 90 and 100% (PASI 75, PASI 90 and PASI 100, respectively) improvement in PASI, compared with baseline, were also recorded. Results At week 12, 63.53% of the patients reached PASI 90 and 49.17% PASI 100. After 3 years of treatment, 65.22% of patients maintained a complete skin clearance, and 91.30% had an absolute PASI of 2 or less. Patients naïve to biological therapies had better clinical responses at weeks 12, 24 and 52. However, after 2 years of treatment, no significant differences were observed. Body mass index did not interfere with the effectiveness of brodalumab throughout the study. No new safety findings were recorded. After 36 months, 85.64% of our patients were still on treatment with brodalumab. Conclusion Our data confirm the effectiveness and the safety of brodalumab in the largest real-life cohort to date, up to 156 weeks.